2012
DOI: 10.1016/j.neuropsychologia.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disrupts the evaluative component of performance monitoring: An ERP study

Abstract: Thirty low and 30 high anxious participants performed a speeded Go/noGo task during which they had to rely on evaluative feedback to infer whether their actions were timely (correct) or not. We focused on FRN, an ERP component that is sensitive to the valence of feedback.Depending on the context, neutral faces served either as positive or negative feedback.Whereas the FRN of low anxious individuals did discriminate between neutral faces when used either as positive or negative feedback, the FRN of high anxious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 60 publications
(99 reference statements)
6
51
5
Order By: Relevance
“…34 The dentists all endorsed feeling at least some degree of anxiety or fear on occasions. Recent laboratory studies have demonstrated 1. that anxiety selectively disrupts the evaluative component of performance monitoring 35 and 2. induced fear reduces digit sensory perception though induced anger had no effect. 36 The possible implications of this for dentists' practical abilities under stress have yet to be evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…34 The dentists all endorsed feeling at least some degree of anxiety or fear on occasions. Recent laboratory studies have demonstrated 1. that anxiety selectively disrupts the evaluative component of performance monitoring 35 and 2. induced fear reduces digit sensory perception though induced anger had no effect. 36 The possible implications of this for dentists' practical abilities under stress have yet to be evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…Goldberg & Fawcett, 2012) which may abolish FRN sensitivity to feedback valence (Aarts & Pourtois, 2012) and increase ERN amplitudes (Hajcak, McDonald & Simons, 2003;Santesso, Segalowitz, & Schmidt, 2006;Weinberg, Klein & Hajcak, 2012). However, anxiety does not seem to affect the ERN (Olvet & Hajcak, 2009) or FRN (Grundler, Cavanagh, Figueroa, Frank, & Allen, 2009) when trial-to-trial feedback is given.…”
Section: Overall Attenuated Frn Amplitudes In Patients With Mddmentioning
confidence: 97%
“…Indeed, such people can have difficulty evaluating their own performance, such that negative and positive performance outcomes both produce similar affective responses and dACC activity [106,107]. Consequently, although trait anxiety is associated with greater conflict-related activity in the dACC [69,70], this activity does not necessarily translate to improved cognitive control.…”
Section: Emotion Is Necessary But Not Sufficient For Recruiting Controlmentioning
confidence: 99%